Malnutrition and cardiovascular risk in haemodialysis patients with chronic kidney disease - da Silva ANDRADE, Iziane; de Magalhães CUNHA, Carla; Passos de BRITO, Beatriz; Chagas Oliveira de FRANÇA, Fabiana; Pereira Magalhães de OLIVEIRA, Lucivalda (Revista de Nutrição, 2023)
Objective To verify the association between nutritional status and traditional and non-traditional cardiovascular risk factors in haemodialysis patients. Methods A cross-sectional study with 132 patients over 18 years of age on haemodialysis to evaluate nutritional status through Subjective Global Assessment. Information on traditional and non-traditional cardiovascular disease risk factors were obtained using a structured questionnaire; the Framingham score was also used to assess cardiovascular risk. Data analysis was performed using the Chi-square Test or Fischer Exact Test and a Log-binomial Regression Model. Results Malnutrition affected 31.1% of patients. Among them, a higher percentage of smokers (p=0.016), former smokers (p=0.034) and diabetes Mellitus patients (p=0.001) were detected. Malnutrition was found to be 4.53 times more prevalent in diabetic individuals (95%CI: 1.99-10.27) and 2.26 times more prevalent among former smokers (95%CI: 1.04-4.95). Malnourished individuals exhibited a 4.03 times prevalence of moderate to severe cardiovascular risk. Conclusion A high prevalence of malnutrition and of other risk factors for cardiovascular disease were observed. Such factors included diabetes Mellitus, smoking and former smoker conditions and were associated with malnutrition. In addition, it was found that malnourished individuals were more likely to develop cardiovascular disease within 10 years.